A rapid appraisal of causes of child death in community settings in district Bhopal - Gour, Devendra; Toppo, Manju; Melwani, Veena; Khan, Amreen; Dohare, Pradeep; Dandotiya, Dileep (International Journal Of Community Medicine And Public Health, 2018)
Background: Child mortality is considered as a core indicator for child health and well-being. SRS (December 2016) has shown that maximum IMR is in Madhya Pradesh which is 50 per 1000 live births and U5MR is 77 per 1000 live birth (2011). The study was carried out with the objectives to list out and categorize medical as well as socio-economic factors associated with these deaths and to evaluate the current status of child deaths in terms of the provision of health services and gaps in planning and execution of these services. Methods: This cross sectional study was conducted on 42 deaths which occurred in Home settings in Bhopal District. A team visited the identified household and conducted in depth interview regarding the entire event related to antenatal care, place of delivery, intranatal and postnatal care, accessibility of the health services and quality of care rendered that contributed to poor child health that resulted in the death of the child. Results: Out of 42 child deaths covered, 23 took place in the neonatal period, of which 21 were home deaths. 47.61% were attended by trained birth attendant. Breastfeeding was started immediately in 94.11% neonates whereas 5.88% were breastfed second day or later. 19 deaths took place in the post neonatal period, of which 17 were home deaths. (68.75%) were breast fed immediately within one hour of birth. Conclusions: A majority of home based child deaths are occurring in families with high illiteracy rates and those belonging to BPL families.